Decent Work Conditions for Domestic Workers in the Employer’s Eyes: Study Results in Makassar, Surabaya, and Bandung - Ida Ruwaida (Yayasan Jurnal Perempuan, 2017)
This article is based on the study on knowledge, attitude, and practice regarding the rights and protections of domestic workers (PRTs) in three cities (Surabaya, Makassar, and Bandung). This paper tries to describe working conditions of PRT, not from the eyes or viewpoint of PRTs, but from their employers. The interesting findings is the tendency of double standards among employers when they faced the social aspects of their relations with PRTs will be transformed into economic ones by promoting the decent work conditions of PRTs. It means domestic workers should be recognized as worker, like others, and their rights will be fulfilled and protected. Assuming the protection of domestic workers is a manifestation of social development, in Indonesian context, the structural intervention through state policy will be conflicted with the social cultural as well as historical aspects of PRTs. Therefore,the study indicates that there is a need to develop social process as apart of cultural intervention for building an equal relationship between domestic workers and their employers.